DIDACTICAL CERTIFICATE OF THE PROCEDUCTIONS OF PROCEDURE TEACHERS CONDITIONS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the process of developing the professional competence of future foreign language teachers and the didactic conditions necessary to ensure it. The importance of linguistic, methodological, communicative, and innovative competencies for foreign language teachers is emphasized, and educational approaches aimed at developing these competencies are presented. Additionally, the role of scientific and methodological support, the use of innovative technologies, practical training, creating a foreign language environment, and continuous education is discussed. The article highlights both theoretical and practical aspects that contribute to improving modern language teaching methods and enhancing the professional training of foreign language teachers.